2016
DOI: 10.1016/j.bbmt.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Chemotherapy and Autologous Hematopoietic Stem Cell Transplantation as Adjuvant Treatment in High-Risk Breast Cancer: Data from the European Group for Blood and Marrow Transplantation Registry

Abstract: The aim of this retrospective study was to assess toxicity and efficacy of adjuvant high-dose chemotherapy (HDC) and autologous hematopoietic stem cell transplantation (AHSCT) in 583 high-risk breast cancer (BC) patients (>3 positive nodes) who were transplanted between 1995 and 2005 in Europe. All patients received surgery before transplant, and 55 patients (9.5%) received neoadjuvant treatment before surgery. Median age was 47.1 years, 57.3% of patients were premenopausal at treatment, 56.5% had endocrine-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…12,13 Recently, Martino et al in an EBMT retrospective analysis, showed that adjuvant HDC with ASCT, in contrast with early studies 14,15 , is a safe procedure with a TRM (Transplant related mortality) that is, in more recent years, less than 1%. 16 This is consistent with what has been observed in modern prospective studies. 17,18 Furthermore, in keeping with previous reports [19][20][21] , the long-term effects of HDC do not differ from those observed with conventional chemotherapy, in particular regarding the risk of secondary cancer.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…12,13 Recently, Martino et al in an EBMT retrospective analysis, showed that adjuvant HDC with ASCT, in contrast with early studies 14,15 , is a safe procedure with a TRM (Transplant related mortality) that is, in more recent years, less than 1%. 16 This is consistent with what has been observed in modern prospective studies. 17,18 Furthermore, in keeping with previous reports [19][20][21] , the long-term effects of HDC do not differ from those observed with conventional chemotherapy, in particular regarding the risk of secondary cancer.…”
Section: Introductionsupporting
confidence: 92%
“…The metastatic potential in TN BC is similar to that of other BC subtypes, but these tumors are associated with a shorter median time to relapse and death, as is also demonstrated in the small cohort of patients included by Martino et al in the EBMT retrospective analysis. 16 While only 27% of pts had HER2 status available, Berry et al conducted an additional (questionable) statistical evaluation, not often utilized in medical oncology, and conclude that "the triple-negative observation is likely to be spurious". 19 A positive effect of HDC in HER2-negative population, particularly in triple-negative tumors, is biologically plausible and supported by clinical evidence.…”
Section: The Prognosis Of Hrbc Has Changed Very Littlementioning
confidence: 99%
“…As discussed in more detail in previous reports [111,194], the overall conclusion is that auto-HCT in BC improves PFS but not OS in most studies. However, auto-HCT may still represent a clinical option for selected patients with specific biological characteristics and/or having gross involvement of axillary nodes (adjuvant setting) or highly chemosensitive disease (advanced setting) [195][196][197][198][199].…”
Section: Al Amyloidosismentioning
confidence: 99%
“…Recent studies suggested a role for HDC and HDC-AHSCT in the context of BC, also in view of the fact that this procedure can now be given safely, but failed to clearly identify the subset of patients who may benefit from HDC AHSCT. [7][8][9] We hypothesized that HDC AHSCT might be particularly beneficial to patients with BRCA genetic inactivation. Thus, we conducted a retrospective study focusing on metastatic breast cancer (MBC) patients receiving HDC AHSCT with the objective to examine the outcome of patients according to the presence of a documented germline BRCA mutation status.…”
Section: Introductionmentioning
confidence: 99%